Implicit Block and Runge- Kutta type Methods for Solution of Second-Order Ordinary Differential Equations. - Badmus A.M,; Subair A.O, (Applied Mathematics and Computational Intelligence (AMCI), 2024)
In this research, implicit discrete schemes which form our block integrators were developed for solving Initial Valued Problems of Ordinary Differential Equations. The equivalent second order Runge-Kutta type Methods (RKTM) were also constructed for the same purpose. Both methods were demonstrated on linear and nonlinear problems of Ordinary Differential Equations. Numerical results obtained from RKTM show that the method is competitive with the existing one.